Evaluasi Pembelajaran Fiqih Berbasis Kulliyatul Mu’allimin Al-islamiyyah di Pondok Pesantren - Syafri Royyan Abdillah; Muhammad Suhirman; Abdul Fattah; Saparudin Saparudin (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
Fiqh learning is one of the essential components of Islamic religious education that must be mastered by students, not only in the cognitive domain but also in the affective and psychomotor domains. Learning outcomes evaluated solely through written assessments cannot necessarily serve as a valid indicator of students’ ability to apply fiqh knowledge correctly in practice. Therefore, a holistic evaluation approach is required. Based on the Kulliyatul Mu’allimin al-Islamiyyah (KMI) curriculum, evaluation can be conducted comprehensively and in depth, enabling meaningful changes in students’ behavior. This study aims to (1) analyze the implementation of KMI-based fiqh learning evaluation in an Islamic boarding school (pesantren), and (2) identify the factors influencing its effectiveness. The study employed a qualitative approach using a narrative inquiry design. The research was conducted from April to May 2026 at Nurul Haramain NWDI Islamic Boarding School. The findings reveal that (1) the evaluation of KMI-based fiqh learning at Nurul Haramain NWDI Islamic Boarding School is conducted through both formative and summative assessments, including written tests, Computer-Based Tests (CBT), oral examinations, and practical assessments. Furthermore, the 24-hour boarding school system constitutes a distinctive advantage, as it enables continuous evaluation through direct observation of students’ daily behavior. (2) The main supporting factors in implementing this evaluation system include the integrated 24-hour boarding school environment, the comprehensive KMI curriculum, the role of teachers as role models, and a strong culture of discipline and habituation. Meanwhile, the challenges encountered include differences in students’ educational backgrounds and abilities, as well as the large student-to-teacher ratio.